3D Carbonaceous Current Collectors: The Origin of Enhanced Cycling Stability for High‐Sulfur‐Loading Lithium–Sulfur Batteries. (29th June 2016) - Peng, Hong‐Jie; Xu, Wen‐Tao; Zhu, Lin; Wang, Dai‐Wei; Huang, Jia‐Qi; Cheng, Xin‐Bing; Yuan, Zhe; Wei, Fei; Zhang, Qiang
Abstract : The cycling stability of high‐sulfur‐loading lithium–sulfur (Li–S) batteries remains a great challenge owing to the exaggerated shuttle problem and interface instability. Despite enormous efforts on design of advanced electrodes and electrolytes, the stability issue raised from current collectors has been rarely concerned. This study demonstrates that rationally designing a 3D carbonaceous macroporous current collector is an efficient and effective "two‐in‐one" strategy to improve the cycling stability of high‐sulfur‐loading Li–S batteries, which is highly versatile to enable various composite cathodes with sulfur loading >3.7 mAh cm −2 . The best cycling performance can be achieved upon 950 cycles with a very low decay rate of 0.029%. Moreover, the origin of such a huge enhancement in cycling stability is ascribed to (1) the inhibition of electrochemical corrosion, which severely occurs on the typical Al foil and disables its long‐term sustainability for charge transfer, and (2) the passivation of cathode surface. The role of the chemical resistivity against corrosion and favorable macroscopic porous structure is highlighted for exploiting novel current collectors toward exceptional cycling stability of high‐sulfur‐loading Li–S batteries. Abstract : A 3D carbonaceous current collector assembled from millimeter‐long carbon nanotubes (CNTs) significantly enhances the cycling stability of lithium–sulfur batteries with high sulfur loading >3.7 mg cm −2, of which the lowest capacity decay rate is 0.029% per cycle upon 950 cycles. The enhancement originates from the high chemical stability and intrinsic macroporous structure of CNTs compared to 2D Al and graphene current collectors.